The mediating role of instrumental activities of daily living between cognitive function and depressive symptoms in community-dwelling older adults: the Arao study - Maiko Nagaoka; Katsuya Nagaoka; Naoto Kajitani; Seiji Yuki; Asuka Koyama; Kazuhiro Yoshiura; Kazuki Honda; Yusuke Miyagawa; Shuken Boku; Noboru Fujise; Minoru Takebayashi (BMC Psychiatry)
Abstract Aim The association between cognitive decline and late-life depression (LLD) is well-reported, but few studies have investigated the mediating factors. This study aimed to identify mediating factors between cognitive function and depressive symptoms (outcome), focusing on IADL, in adults aged 65 years and older. Methods This cross-sectional study included 1,401 community-dwelling Japanese individuals aged ≥ 65 years. LLD was defined using the Geriatric Depression Scale (GDS). Cognitive function was assessed using the Mini-Mental State Examination Test Form (MMSE), and IADL was evaluated using the Tokyo Metropolitan Institute of Gerontology Index of Competence (TMIG-IC). Multiple regression and mediation analyses were conducted by fully adjusted potential confounding factors. Results Among the 1,401 participants, the prevalence of late-life depression was 10.2%. In the adjusted multiple regression analysis, IADL demonstrated a significant correlation coefficient and was significantly associated with depressive symptoms (regression coefficient [β] = -0.33, 95% confidence interval [CI] = -0.39 to -0.26). Cognitive function was also significantly associated with depressive symptoms (β = -0.05, CI: -0.09 to -0.01). In the mediation analysis, IADL scores significantly mediated the relationship between cognitive function and depressive symptoms (estimated indirect effect = -0.1000, bootstrap standard error = 0.0142, bootstrap standard CI = -0.1290 to -0.0737). Conclusions IADL was a mediating factor in the relationship between cognitive function and depressive symptoms, and cognitive function contributed to depressive symptoms through IADL. IADL might play an important role in the prevention and early diagnosis of late-life depression.